2019
DOI: 10.1111/tid.13199
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tigecycline in the treatment of infections caused by carbapenem‐resistant gram‐negative bacteria in pediatric liver transplant recipients: A retrospective study

Abstract: Introduction Tigecycline (TGC) is effective for the infections caused by carbapenem‐resistant gram‐negative bacteria (CRGNB) in adults, but it is not investigated systematically in children because of concern about adverse effects. This study aimed to analyze the effectiveness of TGC in treating CRGNB infections in children after receiving liver transplant. Methods The subjects in this retrospective study were pediatric liver transplant recipients treated with TGC for at least 3 days to fight microbiologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Another concern for pathogens causing infection after transplantation is the emergence of resistant species such as MDR, XDR, and VRE. The results of our studies showed that about 25% of gram-negative species isolated from patients were XDR type; other studies in this eld also pointed to the high incidence of MDR and XDR pathogens after solid organ transplantation [29][30][31].The increase in rates of resistant pathogen species not only affects the e ciency of common antibiotic regimes, but also increases the mortality rate [32,33].Inappropriate administration of antibiotics in empirical conditions, longer hospital and ICU stays, frequent prescription of broad-spectrum antibiotics such as carbapenems and uoroquinolones in treatment of spontaneous bacterial peritonitis conditions before LT, as well as the need for hemodialysis or Continuous Renal Replacement Therapies (CRRT) after LT are among the risk factors for emerging resistant pathogens after LT [25,32].…”
Section: Discussionsupporting
confidence: 62%
“…Another concern for pathogens causing infection after transplantation is the emergence of resistant species such as MDR, XDR, and VRE. The results of our studies showed that about 25% of gram-negative species isolated from patients were XDR type; other studies in this eld also pointed to the high incidence of MDR and XDR pathogens after solid organ transplantation [29][30][31].The increase in rates of resistant pathogen species not only affects the e ciency of common antibiotic regimes, but also increases the mortality rate [32,33].Inappropriate administration of antibiotics in empirical conditions, longer hospital and ICU stays, frequent prescription of broad-spectrum antibiotics such as carbapenems and uoroquinolones in treatment of spontaneous bacterial peritonitis conditions before LT, as well as the need for hemodialysis or Continuous Renal Replacement Therapies (CRRT) after LT are among the risk factors for emerging resistant pathogens after LT [25,32].…”
Section: Discussionsupporting
confidence: 62%
“…As practiced in many health care settings [ 24 ], tigecycline is used for the treatment of carbapenem-resistant Enterobacteriaceae infections, including K. pneumoniae . Tigecycline was found the best choice from the in vitro results reported in the present study as the susceptibility of K. pneumoniae was 81.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al recently described a case series of pediatric liver transplant recipients who received tigecycline for treatment of carbapenem-resistant Klebsiella pneumonia (in 9/13 cases, 69.2%) and Acinetobacter baumannii (4/13 cases, 30.8%). 2 Clinical efficacy, microbiological clearance, and overall mortality rate associated with tigecycline used in combination with other antibiotics were 84.6% (11/13), 69.2% (9/13), and 15.4% (2/13), respectively. 2 There was not serious adverse event related to tigecycline.…”
Section: Tigecycline For Treatment Of Multidrug-resistant Gram-negatimentioning
confidence: 94%
“…2 Clinical efficacy, microbiological clearance, and overall mortality rate associated with tigecycline used in combination with other antibiotics were 84.6% (11/13), 69.2% (9/13), and 15.4% (2/13), respectively. 2 There was not serious adverse event related to tigecycline. 2 [6][7][8] In conclusion, due to the alarming rise in antimicrobial resistance among gram-negative bacteria in general, and especially in transplant recipients, we urge stakeholders and thought-leaders to incentivize research required to establish antimicrobial clinical breakpoints that guide antimicrobial therapy and we strongly encourage the leading scientific committees to harmonize the clinical breakpoints for existing antimicrobial agents.…”
Section: Tigecycline For Treatment Of Multidrug-resistant Gram-negatimentioning
confidence: 94%
See 1 more Smart Citation